Synthesis, Characterization, and Gas Adsorption Performance of Amine-Functionalized Styrene-Based Porous Polymers - Setnickova, Katerina; Jerabek, Karel; Strasak, Tomas; Mullerova, Monika; Jandova, Vera; Soukup, Karel; Petrickovic, Roman; Tseng, Hui-Hsin; Uchytil, Petr (Polymers, 2022)
In recent years, porous materials have been extensively studied by the scientific community owing to their excellent properties and potential use in many different areas, such as gas separation and adsorption. Hyper-crosslinked porous polymers (HCLPs) have gained attention because of their high surface area and porosity, low density, high chemical and thermal stability, and excellent adsorption capabilities in comparison to other porous materials. Herein, we report the synthesis, characterization, and gas (particularly CO2) adsorption performance of a series of novel styrene-based HCLPs. The materials were prepared in two steps. The first step involved radical copolymerization of divinylbenzene (DVB) and 4-vinylbenzyl chloride (VBC), a non-porous gel-type polymer, which was then modified by hyper-crosslinking, generating micropores with a high surface area of more than 700 m2 g-1. In the following step, the polymer was impregnated with various polyamines that reacted with residual alkyl chloride groups on the pore walls. This impregnation substantially improved the CO2/N2 and CO2/CH4 adsorption selectivity.
Keywords: gas separation; CO2 adsorption; hyper-crosslinked porous polymer; dendrimer; amine impregnation